PENGARUH ANALISIS RETURN ON EQUITY, ECONOMIC VALUE ADDED, NET WORKING CAPITAL RATIO TERHADAP HARGA SAHAM INDUSTRI MANUFAKTUR DI BURSA EFEK JAKARTA - Wimba Respatia (EKUITAS (Jurnal Ekonomi dan Keuangan), 2006)
Real stock price actually is depend on the fundamental condition of the company. Investor make some invest decision with buy some stock, before that they must consider about emiten profit, deviden, growth of sale and asset for the time frame.  Beside that, company prospect in the future must be consider. Stock price influence by EVA and financial ratios. In this research we  combines about the influence of financial ratios and EVA to stock prices for the manufacture industries inIndonesia.This study aims to investigate the impact of economic value added, return on equity and net working capital ratio to the stock price of the manufacture industries in BEJ. We used purposive sampling method, with pooled cross sectional during 2001 until 2003 in 52 companies. Multiple regression model was used to test hypthesis with take 3 free variables.The test hypthesis about return on equity, economic value added and net working capital ratio in BEJ during 2001 until 2003, doesn’t put to a test. It’s identification with one variable wich is doesn’t give the influence to the stock price in manufacture industries, the variable is return on equity ratios and the other variables which are give the influence to the stock price are : economic value added and net working capital ratio.